Anisotropic functionalization of upconversion nanoparticles. Issue 18 (27th April 2018) - Ren, Wei; Wen, Shihui; Tawfik, Sherif Abdulkader; Su, Qian P.; Lin, Gungun; Ju, Lining A.; Ford, Michael J.; Ghodke, Harshad; van Oijen, Antoine M.; Jin, Dayong
Abstract : Ligand competition directs heterogeneous bio-chemistry surface and self-assembly for upconversion nanoparticles. Abstract : Despite significant advances toward accurate tuning of the size and shape of colloidal nanoparticles, the precise control of the surface chemistry thereof remains a grand challenge. It is desirable to conjugate functional bio-molecules onto the selected facets of nanoparticles owing to the versatile capabilities rendered by the molecules. We report here facet-selective conjugation of DNA molecules onto upconversion nanoparticles via ligand competition reaction. Different binding strengths of phosphodiester bonds and phosphate groups on DNA and the surfactant molecules allow one to create heterogeneous bio-chemistry surface for upconversion nanoparticles. The tailored surface properties lead to the formation of distinct self-assembly structures. Our findings provide insight into the interactions between biomolecules and nanoparticles, unveiling the potential of using nanoparticles as fundamental building blocks for creating self-assembled nano-architectures.